Should we routinely assess hypothalamic–pituitary–adrenal axis in pediatric patients with Prader–Willi syndrome? - Wędrychowicz, Anna Maria; Doleżal-Ołtarzewska, Katarzyna; Zygmunt-Górska, Agata; Kalicka-Kasperczyk, Anna Urszula; Tyrawa, Katarzyna; Wojcik, Malgorzata; Janus, Dominika; Kot, Adrianna; Lecka-Ambroziak, Agnieszka; Petriczko, Elzbieta; Wielopolska, Joanna; Starzyk, Jerzy (Frontiers in Endocrinology, 2024)
Background: It has been reported that central adrenal insufficiency (CAI) in pediatric patients (pts) with Prader-Willi syndrome (PWS) may be a potential cause of their sudden death. In addition, the risk of CAI may increase during treatment with recombinant human growth hormone (rhGH). Objective: To prevent both over- and under-treatment with hydrocortisone, we evaluated the prevalence of CAI in a large multicenter cohort of pediatric pts with PWS analyzing adrenal response in the low-dose ACTH test (LDAT) and/or the glugacon stimulation test (GST) and reviewing the literature. Methods: Forty-six patients with PWS were enrolled to the study, including 34 treated with rhGH. LDAT was performed at 46 pts, GST at 13 pts. Both tests were conducted in 11 pts. The tests began at 8.00 a.m. Hormones were measured by radioimmunoassays. Serum cortisol response > 181.2 ng/mL (500 nmol/L) in LDAT and > 199.3 ng/mL (550 nmol/L) in GST was considered a normal response. Additionally, cortisol response delta (the difference between baseline and baseline) > 90 ng/mL or doubling/tripling of baseline cortisol were considered indicators of normal adrenal reserve. Results: Three GSTs were not diagnostic (no hypoglycemia obtained). LDAT results suggested CAI in 4 pts, but in 2/4 pts CAI was excluded in GST. GST results suggested CAI in only one patient, but it was excluded in LDAT. Therefore, CAI was diagnosed in 2/46 pts (4.3%), one treated and one untreated rhGH, with the highest cortisol values of 162 and 175 ng/dL, but only in one test. However, based on the cortisol delta response and treplication of basal cortosol, CAI was finally diagnosed in one patient treated with rhGH (2.2%). Conclusion: We present low prevalence of CAI in pediatric patients with PWS, therefore, we do not recommend to screen routinely the function of HPAA in all patients with PWS, both treated and untreated with rhGH. Signs and symptoms or low morning ACTH levels suggestive of CAI, require urgent and appropriate diagnosis of HPAA by stimulation test. Our data indicate that the diagnosis of CAI should be confirmed by at least two tests to prevent overtreatment with hydrocortisone.